THE REQUIREMENTS FOR QUALIFICATION OF DEFENCE COUNSEL IN THE INTERNATIONAL CRIMINAL COURTS AND TRIBUNALS - Gutnyk, Vitalii (Teisė, 2015)
This article examines the requirements for qualification of defence counsel in the International Criminal Court, the International Criminal Tribunal for the former Yugoslavia, the International Criminal Tribunal for Rwanda, the Mechanism for International Criminal Tribunals and the Special Court for Sierra Leone. Particular attention is given to the requirements as to experience, language skills and lack of a criminal record or disciplinary proceedings. The proposals for improvement of the requirements for qualification of defence counsel are made in this article.